Use of Aspiration Method for Collecting Brain Samples for Rabies Diagnosis in Small Wild Animals - Iamamoto, K.; Quadros, J.; Queiroz, L. H. [UNESP] (Wiley-Blackwell Publishing, Inc, 2011)
P>In developing countries such as Brazil, where canine rabies is still a considerable problem, samples from wildlife species are infrequently collected and submitted for screening for rabies. A collaborative study was established involving environmental biologists and veterinarians for rabies epidemiological research in a specific ecological area located at the São Paulo State, Brazil. The wild animals' brains are required to be collected without skull damage because the skull's measurements are important in the identification of the captured animal species. For this purpose, samples from bats and small mammals were collected using an aspiration method by inserting a plastic pipette into the brain through the magnum foramen. While there is a progressive increase in the use of the plastic pipette technique in various studies undertaken, it is also appreciated that this method could foster collaborative research between wildlife scientists and rabies epidemiologists thus improving rabies surveillance.
Keywords: Brain harvest; plastic pipette; rabies diagnosis; wild animals